MODIFIKASI GAYA HIDUP PADA MASA PANDEMI COVID-19 BERSAMA APARAT DESA TATAH LAYAP - Saftia Aryzki; Riza Alfian (Jurnal Bakti untuk Negeri, 2021)
The problem that is happening now is the increasing number of sufferers infectedwith the Covid 19 virus in Indonesia and in the world. South Kalimantan is an areathat occupies 10 provinces with the largest increase in the number of exposed toCovid-19. This is greatly influenced by the implementation of health protocols. Inimplementing health protocols, one of them is by modifying the lifestyle during thecurrent pandemic.This lifestyle modification is carried out to maintain and improvetheir health, prevent the risk of disease and play an active role in the public healthmovement, especially for village officials as a model for community movement inthe village. The activities carried out were in the form of providing information tovillage officials about counseling activities about lifestyle modifications during thepandemic. The results of the counseling are known to the public that theyunderstand the importance of lifestyle modifications and indicators in improvinghealth